ANALISIS YURIDIS PENGGANTIAN HAKIM MAHKAMAH KONSTITUSI DALAM MASA JABATANNYA OLEH DEWAN PERWAKILAN RAKYAT - Suhendri, Dicky (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The Constitutional Court is a high state institution in the Indonesianconstitutional system which has constitutional authority to adjudicate at the firstand final level to decide disputes over the authority of state institutions, thedissolution of political parties, disputes over general election results, and judicialreview of the 1945 Constitution. The constitution acts as the guardian of theconstitution whose task is to ensure that all legal products and actions of stateinstitutions do not conflict with the constitution.This research is normative research. This is based on library researchwhich takes quotations from reading books, or supporting books that are relatedto the problem to be researched. This research uses secondary data sourcesconsisting of primary, secondary and tertiary book materials. This research alsouses qualitative data analysis and produces descriptive data.From the results of the research and discussions carried out, severalconclusions were obtained, namely: First, Article 10 paragraph (1) PMK 4/2012clearly states that the replacement or removal of Constitutional Court Judgesfrom their positions can only be carried out by presidential decree at the requestof the chairman of the Constitutional Court ., Second, the removal ofConstitutional Judge Aswanto by the DPR is an attempted intervention against theConstitutional Court Judge, in this case the Judicial Authority should havefreedom and independence in carrying out the duties and functions of theConstitutional Court. So it can be concluded that the dismissal of Judge Aswantoand appointing Guntur Hamzah as Constitutional Court Judge is not can bejustified because it is contrary to law. The author's suggestion is that thePresident is expected to show firmness in handling the replacement ofConstitutional Justice Aswanto. In this case, the President is not obliged to payattention to the letter from the DPR regarding the replacement of ConstitutionalJustice Aswanto with Guntur Hamzah, or provide a response that the Presidentcannot carry out the replacement because the process is wrong.Keywords: Constitutional Court-Replacement of Judges-People'sRepresentative